Public Relations Strategy in Building Brand Awareness: A Case Study of KDS - Abdul Chamid (Komunitas Dosen Indonesia, 2024)
This research aims to investigate the public relations strategies employed by PT Kefa Dadali Sinergindo (KDS), a nascent company in the food and renewable energy industry, to enhance its brand visibility. Established in late 2020, the company specializes in the production and distribution of coconut shell briquettes and banana snacks. Employing a descriptive qualitative approach, this research delves into the company's public relations strategies. This methodology enables an in-depth exploration of the underlying meanings and nuances within the collected data. Through direct observation and in-depth interviews, the researcher aims to gain a comprehensive understanding of the company's public relations tactics. The findings of this research reveal that KDS predominantly utilizes a soft selling or indirect sales approach to foster brand awareness. Key strategies employed by the company include: 1) Press Releases: The company actively disseminates information about its products, services, and corporate activities through various media channels, including print and online publications; 2) Press Conferences: These events are convened to announce significant company developments, such as product launches or major milestones; 3) Launching Events: These events are designed to introduce new products to target consumers and media representatives. By effectively implementing these public relations strategies, KDS has successfully cultivated a positive brand image and garnered significant public attention.